2021
DOI: 10.1186/s40813-021-00242-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an increased content of pea and yellow lupin protein in the diet of pigs on meat quality

Abstract: Background The aim of the study was to test the effect of replacing soya beans with pea and yellow lupin seeds in the diet of pigs on meat quality. The meat for the tests was obtained from 60 fattening crossbred pigs F1 (Polish Large White × Polish Landrace)  × F1 (Pietrain × Duroc). The animals belonged to three feeding groups depending on the feed used with the total share of soybeans and its reduction. Water holding capacity, colour, and tenderness were measured and visual and tactile evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…There were no significant differences between the of meat obtained from pigs fed with fodder with the addition of raw lupine, fermented lupine, or fodder with soy. Similar results were reported by Cebulska et al [61], showing that lupine can replace soy in food intended for pigs.…”
Section: Soysupporting
confidence: 90%
See 1 more Smart Citation
“…There were no significant differences between the of meat obtained from pigs fed with fodder with the addition of raw lupine, fermented lupine, or fodder with soy. Similar results were reported by Cebulska et al [61], showing that lupine can replace soy in food intended for pigs.…”
Section: Soysupporting
confidence: 90%
“…Cebulska et al [61] investigated the effects of replacing soy protein in pig diets with pea protein and yellow lupine. Compared with the animals in the control sample, the meat from legume-fed pigs had a more favorable proportion of exogenous amino acids (except methionine), and higher amounts of micronutrients such as zinc and iron.…”
Section: Soymentioning
confidence: 99%
“…Outcomes similar to our results were highlighted by Mikulski et al (2014), who reported that the meat of chickens fed a 180 g/kg LP diet was harder and chewier than groups fed an LP-free diet. A high shear force of meat was also confirmed in pigs and cattle fed LP as a substitute for SBM (Kennedy et al 2018;Cebulska et al 2021). This could be due to the increased collagen content in the meat of animals fed an LP-supplemented diet (Laudadio and Tufarelli 2011;Banaszak et al 2020), which affects the structure and diameter of muscle fibers tissues, as well as the thickness of the meat (Lepetit 2008).…”
Section: Discussionmentioning
confidence: 77%